The spectacle of isolation in horror films : dark parades - Royer, Carl (Haworth Press, 2005)
Go behind the scenes with an insightful look at horror films?and the directors who create them The Spectacle of Isolation in Horror Films: Dark Parades examines the work of several of the genre's most influential directors and investigates how traditional themes of isolation, alienation, death, and transformation have helped build the foundation of horror cinema. Authors Carl and Diana Royer examine the techniques used by Alfred Hitchcock that place his work squarely in the horror (rather than suspense) genre, discuss avant-garde cinema's contributions to mainstream horror, explore.